Comparison of Antiglycation and Antioxidant Potentials and Total Phenolic Contents of Decoctions from Antidiabetic Plants - Perera, P.R.D.; Ekanayake, S.; Ranaweera, K.K.D.S. (Procedia Chemistry, 2015)
Attached